PENGARUH DISTRIBUTION COSTS TERHADAP SALES PADA PERUSAHAAN TEKSTIL DAN PAKAIAN JADI DI BEI PERIODE 2020-2024 - Rohyana, Cahyat; Hudawiyah, Zia Zakia (LAND JOURNAL, 2026)
The decline in sales in Indonesia's textile and apparel industry in recent years has been influenced by competition from low-priced imported products and shifts in consumer shopping patterns. This situation demands companies to manage distribution costs efficiently to maintain sales performance. This study is conducted to evaluate the influence of distribution expenses on sales in textile and apparel companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The methodological framework of this study is based on a quantitative approach, making use of panel data regression analysis carried out with EViews software. The sample was acquired through purposive sampling of 12 enterprises, utilizing quarterly financial report data. This research demonstrates that distribution expenses play an important role in shaping sales performance, where the degree of influence differs in line with the strategic approaches and specific situations of the companies observed. These findings emphasize the importance of optimizing distribution to support competitiveness in a dynamic market. Keywords: distribution costs, sales, textile industry, IDX